Explore - Dwojak, Adam (Instal, 2025)
The energy transition is slowly gaining momentum. In view of the anticipated changes, particularly the planned reduction in the operating temperatures of district heating networks, some changes can be expected in this field. For some unknown reason, the available studies so far deal in generalities without much in the way of specifics. At the very least, it would be useful to set out some guidelines for future district heating networks.